AB1269 Quality standard for the management of patients with psoriatic arthritis: quantum project. (12th June 2018) - Oton, T.; Loza, E.; Beltrán, E.; Díaz-Miguel, C.; Fernández-Carballido, C.; Galíndez, E.; García Porrua, C.; Gratacós, J.; Medina, J.; Queiro, R.; Ramírez, J.; Reina, D.; et al.
Abstract : Background: In the context of complex diseases like psoriatic arthritis (PsA), in which patients are often followed by different professionals, it is important for health professionals, providers and patients to have tools for delivering and demanding optimal care. One way to organise and evaluate health care quality is by the use of validated standards of care and quality indicators. Objectives: To develop nationally accepted standards of care and quality indicators for care in PsA. Methods: Qualitative methodology was followed that included: 1)Two focus groups (one with patients with PsA and another with non-rheumatologists specialists involved in the care of patients with PsA; 2) A narrative literature review of published documents related to the quality of care in PsA (including the QUANTUM Report 1 ); 3) A nominal group meeting in which 15 expert rheumatologists generated and consensuated, a series of quality criteria as well as formulas or quantifiable objective measures to evaluate them; 4) A Delphi to establish the feasibility, priority and agreement with the quality criteria; 5) A final generation of standards of care and their attributes (including quality indicators). A descriptive analysis of the results was carried out. Results: A total of 59 standards of care were generated, 19 of mandatory compliance, grouped into 4 blocks according to specific objectives: 1) Early diagnosis (n=6); 2) optimising the management of the disease (n=26), 3) multidisciplinary collaboration (n=9); 4) monitoring improvement (n=18). To assess the compliance of these standards of care, in many cases the medical records will be reviewed. Other sources will be the memory of the service and hospital and bibliographic databases. Regarding to the level compliance, for some of the standards of care this is yes/no, for others the compliance will range are from 50% to 100%, and in this range for many this will be by 80%. Conclusions: This set of standards of care should help improve quality of care in APs patients. Reference: [1] Favier G, Gladman DD, Merola JF, Armstrong AW, Boehncke WH, Helliwell PS. Benchmarking Care in Psoriatic Arthritis – The QUANTUM Report: A Report from the GRAPPA 2016 Annual Meeting. J Rheumatol. 2017;44(5):674–8. Disclosure of Interest: None declared